2008
DOI: 10.1016/j.jtcvs.2007.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic changes in ascending aorta and risk factors related to histopathologic conditions and aortic dilatation in patients with tetralogy of Fallot

Abstract: The majority of aortic media of the ascending aorta in cyanotic tetralogy of Fallot indicates significant loss of lamellar units and pre-existing intrinsic aortopathy. The changes are present since infancy and are more pronounced in older patients subjected to long-standing cyanosis and volume overload and may account for or may coexist with the higher incidence of aortic dilatation encountered in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 23 publications
4
40
1
Order By: Relevance
“…Chowdhury et al, reported aortic diameter measured by echocardiography showed significant dilatation in 66.3% of unrepaired patients with TOF in one publication and 68.9% in another publication [38]. In our study, aortic root diameter measured by MDCT showed significant dilation in 70% of unrepaired TOF patients.…”
Section: Aortic Root Dilatation In Unrepaired Tetralogy Of Fallotsupporting
confidence: 60%
See 3 more Smart Citations
“…Chowdhury et al, reported aortic diameter measured by echocardiography showed significant dilatation in 66.3% of unrepaired patients with TOF in one publication and 68.9% in another publication [38]. In our study, aortic root diameter measured by MDCT showed significant dilation in 70% of unrepaired TOF patients.…”
Section: Aortic Root Dilatation In Unrepaired Tetralogy Of Fallotsupporting
confidence: 60%
“…Chowdhury et al, demonstrated the presence of MAPCAs in (52.9%) of 51 patients with aortic root dilatation. Medionecrosis, one of the histological abnormalities of the aortic media in dilated aorta was more prevalent in patients with presence of MAPCAs [38]. In our study 54.29% of 35 patients with aortic root dilatation had MAPCs and or PDA.…”
Section: Aortic Root Dilatation In Unrepaired Tetralogy Of Fallotsupporting
confidence: 50%
See 2 more Smart Citations
“…In addition, also genetic predisposition might contribute to aortic dilatation. It could, for instance, be shown that fibrillin-1 genetic mutations in TOF patients are associated with histologic abnormalities and larger aortic size [3][4][5].…”
Section: Introductionmentioning
confidence: 99%